Decision Support System in Determining TPQ/TQA Teacher Certification Categories Using the SAW Method - Zikri, Afdal; Nurcahyo, Gunadi Widi; Sumijan, S (Universitas Putra Indonesia YPTK Padang, 2025)
TPQ/TQA teacher certification is an effort to improve the quality of educators in deepening their knowledge of the Qur'an. The certification assessment process often faces challenges related to subjectivity and inconsistencies in criteria, thus requiring a decision support system capable of producing more objective and measurable assessment results. Based on the problems described above, this study aims to analyze the TPQ/TQA teacher certification assessment in Padang City. The SAW method is very suitable for this study because of its ability to perform calculations based on predetermined criteria. The research data consists of 60 assessment documents. The analysis process includes determining criteria, normalizing weights, calculations, and rankings. Based on the 60 datasets, 9 individuals obtained a certification score of A, 11 obtained a B, and 40 obtained a C. The results of this study indicate that the decision support system is capable of providing highly accurate, transparent, and efficient results in determining TPQ/TQA teacher certification scores. These findings are expected to be useful for TPQ/TQA management institutions in determining certification scores.